2021
DOI: 10.1007/978-3-030-72240-1_14
|View full text |Cite
|
Sign up to set email alerts
|

How Do Users Revise Zero-Hit Product Search Queries?

Abstract: A product search on an e-commerce site can return zero hits for several reasons. One major reason is that a user's query may not be appropriately expressed for locating existing products. To enable successful product purchase, an ideal e-commerce site should automatically revise the user query to avoid zero hits. We investigate what kinds of query revision strategies turn a zero-hit query into a successful query, by analyzing data from a major Japanese e-commerce site. Our analysis shows that about 99% of zero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The gen./specialization and aspect change transformations fall into the former type, whereas all other categories fall into the latter. We highlight here that unlike previous categorizations that describe how users revise queries in e-commerce [3,26], how to generate better queries to substitute the original query [28], how users reformulate queries in a session [27], we study here how to categorize query variations for the same information need which is a related but different problem.…”
Section: Uqv Taxonomymentioning
confidence: 99%
See 1 more Smart Citation
“…The gen./specialization and aspect change transformations fall into the former type, whereas all other categories fall into the latter. We highlight here that unlike previous categorizations that describe how users revise queries in e-commerce [3,26], how to generate better queries to substitute the original query [28], how users reformulate queries in a session [27], we study here how to categorize query variations for the same information need which is a related but different problem.…”
Section: Uqv Taxonomymentioning
confidence: 99%
“…The three methods in this category add one spelling error to the query; the query term an error is introduced in is chosen uniformly at random. NeighbCharSwap Swaps two neighbouring characters from a random query term (excluding stopwords 3 ). RandomCharSub Replaces a random character from a random query term (excluding stopwords) with a randomly chosen new ASCII character.…”
Section: 21mentioning
confidence: 99%
“…The inter-annotator agreement [14] was moderate (Cohen's κ = 0.42); the disagreements were highest for the naturality and paraphrasing categories. We found that a total of 56 {q i , q j } pairs had more than one category assigned to it 3 . The resulting distribution is shown in Table 2 (right-most column); the categories of query variations that change the query without changing its semantics account for 57% of all the transformations.…”
Section: Paraphrasingmentioning
confidence: 88%
“…The gen./specialization and aspect change transformations fall into the former type, whereas all other categories fall into the latter. We highlight here that unlike previous categorizations that describe how users revise queries in e-commerce [3,24], how to generate better queries to substitute the original query [26], how users reformulate queries in a session [25], we study here how to categorize query variations for the same information need which is a related but different problem.…”
Section: Uqv Taxonomymentioning
confidence: 99%